I-Pad Based Arabic Language Teaching Method in Al-Azhar Cairo Islamic Senior High School Palembang Indonesia - Diah Sakinah (Ittishal Educational Research Journal, 2020)
We are now living in 21st century, the century of development of technology, datas and digital trends. Several kinds of job have been replaced by their digital versions. Electronic based learning method has been a familiar skill found at majority of school in this century. The motive behind this method is to reduce the illiteracy of technology among students by introducing them how to use some technological devices effectively so they can understand, evaluate and participate on it. In addition for the method of Arabic teaching in Indonesia should be changed into e-learning based as a way to face recent challenges and problems while teaching. One of those problems is the less attention from students to learn Arabic language due to some difficulties of Arabic language teaching books and its material, as well as limited devices they can use. It’s known that this Islamic boarding school is the only school signed up its name on iTunes U platform. This paper is a descriptive qualitative research which took respondents of 10 students of Al-Azhar Cairo Islamic Senior High school Palembang, Indonesia. The data are collected based on interviewing, informing and collecting files. The data collection is completed using Miles and Huberman’s data collection method in descriptive explanation. Finally this research concluded that the iPad based learning method used by this school did impacted well on gaining student’s attention in learning Arabic language including its basic skills (listening, reading, speaking, and writing)